Donor‐influenced Structure–Activity Correlations in Stoichiometric and Catalytic Reactions of Lithium Monoamido‐Monohydrido‐Dialkylaluminates. Issue 39 (13th June 2018) - Lemmerz, Lara E.; McLellan, Ross; Judge, Neil R.; Kennedy, Alan R.; Orr, Samantha A.; Uzelac, Marina; Hevia, Eva; Robertson, Stuart D.; Okuda, Jun; Mulvey, Robert E.
Abstract: A series of heteroleptic monoamido‐monohydrido‐dialkylaluminate complexes of general formula [ i Bu2 AlTMPHLi⋅donor] were synthesized and characterised in solution and in the solid state. Applying these complexes in catalytic hydroboration reactions with representative aldehydes and ketones reveals that all are competent, however a definite donor substituent effect is discernible. The bifunctional nature of the complexes is also probed by assessing their performance in metallation of a triazole and phenylacetylene and addition across pyrazine. These results lead to an example of phenylacetylene hydroboration, which likely proceeds via deprotonation, rather than insertion as observed with the aldehydes and ketones. Collectively, the results emphasise that reactivity is strongly influenced by both the mixed‐metal constitution and mixed‐ligand constitution of the new aluminates. Abstract : Its Al in the design : Access to the lithium centre appears to be a key factor in the efficiency of donor‐supported aluminates in catalytic hydroborations of carbonyl substrates with pinacolborane, while inclusion of a TMP ligand in their design facilitates multifunctional behaviour in the form of metallation.